Common Rangeland Plants of West Central Texas - Clendenin, George (Book collections on Project MUSE., 2016)
Well-managed ranch lands or rangeland in Texas capture the rain that permeates our soils, sustains creeks and rivers, and replenishes aquifers, which, in turn, water our cities. The stewardship of the region is the focus of this book-the largest contributing watershed in the Colorado River Basin-viewed through the lens of its plant communities. This field guide and management reference to four million acres of rangeland in the Concho River watershed of west central Texas offers general descriptions of more than 200 plant species, including information about the plant's growing period, growth.